CINE COLABORATIVO. DISCURSOS, PRÁCTICAS Y MULTIPLATAFORMA DIGITALES. HACIA UNA DIVERSIFICACIÓN DE FORMATOS TRANSMEDIA PARTICIPATIVOS EN EL ESPACIO DIGITAL EUROPEO - Virginia VILLAPLANA RUIZ (Fonseca, Journal of Communication, 2023)
This article aims at the analysis of the new paranoma of collaborative discourses and practices in the European Digital Space. The three themes are collaborative audiovisual production and experience to configure social imaginary; modes of transmission and reception of images related to the processes of collective thinking; and co-learning as a political strategy in the framework of media education